PRAKTIKALITAS PENUNTUN PRAKTIKUM TAKSONOMI INVERTEBRATA BERBASIS PENDEKATAN SAINTIFIK UNTUK MAHASISWA - Anggun Sophia (Unika Santu Paulus Ruteng, 2018)
The purpose of this study is to develop a practice guide invertebrate taxonomic based on a scientific approach for students practical. This type of research is a development study using a Plomp development model consisting of three stages, namely preliminary research, prototyping (prototyping phase) and assessment phase. This study is limited to the prototype-making stage to see the practicality of using practice guides invertebrate taxonomic based on a scientific approach for students. Practicality data were taken in three stages of testing, one-to-one evaluation, small group trial, and large field test. The instrument used is a questionnaire of student practice, questionnaire of lecturer practice. The results showed that the practical guides developed were practical. In the one-to-one test, the results from one to one evaluation get a positive response. This is because students feel the guiding guides developed are good. In the small group test, the average questionnaire is 3.50 (very practical). In the large group test, the average questionnaire of the lecturer practicum and counselor is 3.79 (very practical) and the average questionnaire of student questionnaire is 3.88 (very practical).